Use of the Silastic Sheath in Bladder Neck Reconstruction - D.A. Diamond; G.F. Quimby; R.C. Rink; P.G. Ransley (The Scientific World Journal)
OBJECTIVE: The study compared two populations of patients undergoing bladder neck reconstruction using the silastic sheath in two major pediatric centers. The success with this technique was markedly different in the two centers. The purpose of the study was to determine factors that might explain the divergent results.PATIENTS AND METHODS: Fifteen patients treated in Indianapolis were compared with 94 patients treated in London with the silastic sheath technique of bladder neck reconstruction. Eighty-seven percent of the Indianapolis patients had myelomeningocele whereas 86% of the London group had exstrophy/epispadias. Median age of the Indianapolis patients was 11 years whereas it was 8.4 years in London. Seventy-three percent of patients in Indianapolis were female and 79% in London were male. Patients were followed for a minimum of eight years in Indianapolis and a mean of seven years in London. Similar surgical technique was employed in the two centers but, over time, the London approach included use of a non-reinforced silastic wrapped loosely around the bladder neck with the interposition of omentum. RESULTS: Both groups achieved continence rates exceeding 90%. Of the Indianapolis patients, two-thirds experienced erosion of the silastic at a mean of 48 months. With modifications in the London technique, the erosion rate of silastic was lowered from 100% to 7%. CONCLUSION: Direct, snug wrap of silastic without omentum around the Young-Dees tube as well as simultaneous bladder augmentation placed patients at increased risk for erosion. The silastic sheath technique may be less applicable to myelomeningocele patients. It seems most applicable to older male patients with exstrophy or epispadias undergoing Young-Dees bladder neck reconstruction who have the ability to void.